Setting Cut-Scores: A Critical Review of the Angoff and Modified Angoff Methods - Ricker, Kathryn L. (Alberta Journal of Educational Research, 2006)
The purpose of this article is to review critically the Angoff (1971) and modified Angoff methods for setting cut-scores. The criteria used in this review were originally proposed by Berk (1986). The assumptions of the Angoff method and other current issues surrounding this method are also discussed. Recommendations are made for using the Angoff method. In addition, several issues that are relevant to cut-score setting that are not addressed by Berk’s criteria arose while reviewing the Angoff method. These issues are addressed separately.